2020
DOI: 10.1136/archdischild-2019-318474
|View full text |Cite
|
Sign up to set email alerts
|

Propofol for endotracheal intubation in neonates: a dose-finding trial

Abstract: ObjectiveTo find propofol doses providing effective sedation without side effects in neonates of different gestational ages (GA) and postnatal ages (PNA).Design and settingProspective multicentere dose-finding study in 3 neonatal intensive care units.PatientsNeonates with a PNA <28 days requiring non-emergency endotracheal intubation.InterventionsNeonates were stratified into 8 groups based on GA and PNA. The first 5 neonates in every group received a dose of 1.0 mg/kg propofol. Based on sedative effect and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 32 publications
(75 reference statements)
0
24
1
1
Order By: Relevance
“…15,17 Finally, MBP below 30 mm Hg is used to define hypotension, because some studies found loss of cerebral autoregulation below this threshold. 16,18,19 In our study and in the study of Smits et al, 13,14 were not as haemodynamically stable as they were presumed to be.…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…15,17 Finally, MBP below 30 mm Hg is used to define hypotension, because some studies found loss of cerebral autoregulation below this threshold. 16,18,19 In our study and in the study of Smits et al, 13,14 were not as haemodynamically stable as they were presumed to be.…”
Section: Discussioncontrasting
confidence: 65%
“…Neonates from the previously published NEOPROP‐2 trial were considered for inclusion 14 . The NEOPROP‐2 trial was a prospective multicentre dose‐finding trial conducted at three level III Neonatal Intensive Care Units in the Netherlands.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations